Effect of pH and Temperature on Bacillus sp. R2 Chitinase Activity and Stability. (2016) - Cheba, Ben Amar; Zaghloul, Taha Ibrahim; EL-Mahdy, Ahmad Rafik; EL-Massry, Mohamad Hisham
Abstract: The purified chitinase of Bacillus sp. R2 showed a molecular weight of 41.68 KDa, an optimal pH and temperature of 7.5 and 40 °C respectively. The enzyme was stable between pH 7 to 8 but it lost 57% and 62% of its initial activity at the pH 6 and 9 respectively. The purified chitinase also exhibited complete heat stability for 1 h at 40 °C and retained above 50% and 30% of its original activity after 30 min heating at 50 °C and 60 °C respectively. The chitinase activation energy for chitin hydrolysis was 12.93 Kcal/mol. To the best of our knowledge, this is the first study about marine chitinase characterization from novel gram variable Bacillus isolated from the Red sea.